Conceptualizing Well-Being in Vocational Psychology: A Model of Fulfilling Work. (February 2019) - Allan, Blake A.; Owens, Rhea L.; Sterling, Haley M.; England, Jessica W.; Duffy, Ryan D.
Following from the strengths-based inclusive theory of work (S-BIT of Work), fulfilling work is a central goal of career and work counseling. However, vocational psychologists have yet to develop a comprehensive model of fulfilling work. We addressed this concern by reviewing the literature on well-being, developing the fulfilling work construct, and delineating an operationalized model of fulfilling work. This operationalization contains four components: (a) job satisfaction, (b) meaningful work, (c) work engagement, and (d) workplace positive emotions. These components capture the hedonic, eudaimonic, cognitive, and affective dimensions of fulfilling work. Researchers can adapt these components to different cultures by adjusting their operationalizations and understanding how people interpret and experience fulfilling work in different contexts. Fulfilling work represents the core experience of well-being in the work context and provides a starting point for research on the S-BIT of Work.